Komunikasi Lingkungan pada Pengelolaan Sistem Pertanian Rawa Lebak - Icuk Muhammad Sakir; Lestari, Puji (Jurnal Pekommas, 2022)
This study aims to analyze the implementation of the selection of environmental communication channels in disseminating information on the Lebak swamp farming system, based on environmental conservation. The object of this research is a communication channel with the research subjects of Agricultural Extension Officers (PPL)/Plant Destruction Organism Controls (POPT) as informants. This research is qualitative with case study analysis. Researchers used depth interviewing techniques, Focus Group Discussion (FGD), observation, document analysis, and data analysis techniques using an interactive model. The results of the study stated that 1) The environmental communication process carried out by PPL/POPT was oriented towards community empowerment by enabling participatory and dialogical communication; 2) Activities to stimulate environmental communication of social movements for environmental preservation involving face-to-face channels and media; and 3) The implementation of the use of effective communication channels in conveying messages about environmental conservation manifested in responding to problems and complaints, supporting empathy and the performance of Gabungan Kelompok Tani (Gapoktan). The study's conclusion states that face-to-face communication channels are more than practical between media communication, primarily to support environmental conservation social movements. This research contributes in the form of a dialogical and participatory environmental communication policy to the extension community and the Agriculture Office of Ogan Ilir Regency, South Sumatra.